Dilemma of a Widow as a Ruler in The Duchess of Malfi - Karim, Sajjadul (EAST WEST JOURNAL OF HUMANITIES, 2011)
The Duchess of Mlfi is a revenge tragedy. but Webster has used the fount for much more than just its entertaining value. He has utilized it as a vehicle for the exploration of some themes relevant to the society of his time. Women and questions contenting feminine nature are rued to signify troubling social and political issues of the day. The play deals. in different ways, with haunt of political instability and MISIOICIS a rhetoric of femininity and feminine nature which complements the political aspects of the drama. It moves around a female protagonist. and her predicament shows how the theme of the play are constructed by Webster’s thinking about social Issues of his day. Ironically, he was making points about womett’s rights at a time When only men were alltnm:d In act on the stage. This ankle tries to analyse the relationship between Jacobean society and a widow. the minus surrounding marriage, the freedom of women, and the state of patriarchy in England.